THE ROLE OF GENERATIVE GRAMMAR IN THE PROCESS OF LANGUAGE LEARNING - Shamsiddinov Murod Zubaydullaevich (Western European Studies, 2025)
Generative grammar, proposed by Noam Chomsky, plays a crucial role in language learning by explaining the mechanisms of speech formation based on innate grammatical structures. This article explores the fundamental principles of generative grammar and its application in foreign language learning. Special attention is given to the impact of this theory on modern educational technologies, artificial intelligence, and natural language processing. The study examines ways to integrate generative grammar into adaptive learning systems and machine learning algorithms, enhancing language acquisition methods
Keywords: Generative grammar; language learning; Noam Chomsky